Examination of students' written mathematical communication skills in addressing gender-based open-ended problems - Susilowati, Indri; Cholily, Yus Mochamad; Rosyadi, Alfiani Athma Putri; In'am, Akhsanul (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
Written mathematical communication skills are an important concern in mathematics education. One way to assess these skills is by presenting students with open-ended problems. This study examines differences in written mathematical communication skills based on gender. The purpose of this study is to describe students’ written mathematical communication skills in solving open-ended problems from a gender perspective. The research employed a descriptive qualitative approach, with participants consisting of Grade VIII students from SMPN 2 Pamekasan, categorized into low, medium, and high levels of written mathematical communication skills. Data were collected through open-ended problem-solving tests to analyze students’ written mathematical communication based on gender. The findings indicate that: (1) students in the low-ability category were unable to fully meet the indicators, with both males and females scoring 58; (2) students in the medium-ability category were moderately able to meet the indicators, with both males and females scoring 75; and (3) students in the high-ability category demonstrated strong performance in meeting the indicators, with males scoring 83 and females 100. These results suggest that high-ability students are more effective in meeting the indicators of written mathematical communication, with observable differences based on gender. Female students tend to excel in written narratives, whereas male students show greater strength in visualization. Students with low and medium abilities still require support in notation, image proportion, and written explanations.